2021
DOI: 10.3855/jidc.13757
|View full text |Cite
|
Sign up to set email alerts
|

9-12 months short treatment for patients with MDR-TB increases treatment success in Kyrgyzstan

Abstract: Introduction: MDR/RR-TB is a growing problem in Kyrgyzstan. In 2005, the country introduced standard or individualized treatment for 20-24 months. Because of poor treatment outcomes, in 2017 a short treatment with strict eligibility criteria was introduced. The aim of this study was to compare characteristics and treatment outcomes of MDR/RR-TB patients receiving short (9-12 months) treatment in 2017 with those receiving standard or individualized (20-24 months) treatment in 2016/2017. Methodology: A com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 23 publications
(26 reference statements)
1
14
0
Order By: Relevance
“…Our results align with success rates (ranging from 75 to 90%) reported in other countries for RR/MDR-TB patients treated with all oral mSTR [18,19]. Importantly, the treatment success achieved with this simpli ed mSTR, utilizing Bdq, Lfx and Lzd as core drugs, and Cfz and Cs as companion drugs, appears to provide more favorable outcomes than those found in Central Asia.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our results align with success rates (ranging from 75 to 90%) reported in other countries for RR/MDR-TB patients treated with all oral mSTR [18,19]. Importantly, the treatment success achieved with this simpli ed mSTR, utilizing Bdq, Lfx and Lzd as core drugs, and Cfz and Cs as companion drugs, appears to provide more favorable outcomes than those found in Central Asia.…”
Section: Discussionsupporting
confidence: 87%
“…Tuberculosis (TB), one of the most prevalent infectious diseases globally, continues to exert a signi cant burden on mortality and morbidity. In 2022 TB ranked as the second-largest infectious killer worldwide, surpassed only by coronavirus disease (COVID- 19). It was reported as the primary cause of death among people with the human immunode ciency virus (HIV) and a signi cant contributor to deaths related to antimicrobial resistance [1].…”
Section: Introductionmentioning
confidence: 99%
“…This finding was in line with the previous studies conducted elsewhere. For example, a study from Kyrgyzstan has reported that there was higher 1-month SCC among patients treated with STR than those who were treated with LTR (Zhdanova et al, 2021). Likewise, an almost two-fold greater likelihood of SCC by 2 months following treatment of MDR-TB patients with STR has been reported from Uzbekistan (du Cros et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…As fluoroquinolones (FQs) are considered the backbone of MDR-TB treatment, the presence Mfx in STR which is comparatively more potent and effective than Lfx (present in LTR) against both susceptible and resistant MTB strains (Maitre et al, 2017;Du et al, 2019) could be one of the potential causes of early SCC and better cure rate in patients treated with STR. The presence of strong bactericidal agents like CFZ, and high dose INH which can retain activity against INH resistance due to inhA or katG 315 mutations could be the other possible cause of superior anti-microbial activity by STR (Van Deun et al, 2018;Du et al, 2019;Zhdanova et al, 2021). In current study, the mortality rates in the STR (9.9%) and the LTR (18.3%) were in compliance with the elsewhere reported mortality ranges for MDR-TB patients treated with STR (5.6%-7.8%) (Aung et al, 2014;Kuaban et al, 2015;Khan et al, 2017;Trébucq et al, 2018) and LTR (9.5%-25%) (Ahmad et al, 2015;Rao et al, 2015;Javaid et al, 2017c;Khan et al, 2019;Khan, et al, 2022a).…”
Section: Discussionmentioning
confidence: 99%
“…Even though, the cost-effective directly observed therapy (DOT) strategy highly helps many world countries in controlling and preventing the disease; however, the prevalence of DR-TB has been increasing in the last 15 years, especially in poor economic countries due to a shortage of effective diagnostic and treatment access ( 8 , 10 ).…”
Section: Introductionmentioning
confidence: 99%